The Effect of Organizational Support in Developing the Creative Capabilities of a Faculty Member: Applied Study at the Faculty of economic, Commercial and Management Sciences at Jijel University - Nedjmi, Aissa; Boutaleb, Djahid (Finance and Business Economies Review, 2022)
This study aimed to identify the nature of the impact of organizational support on the creative abilities development in the Faculty of Economic, Commercial and Management Sciences at jijel university from the viewpoint of the faculty members, where the questionnaire was relied on as a tool for data collection, from a sample which contain 80 members who were selected by a simple random sampling method, and the data was processed using the SPSS program. The results of this study revealed that there is a high level of organizational support and creative abilities from the viewpoint of the faculty members in the faculty under study. Also, The study showed that organizational support has a positive effect on creative abilities development at the faculty members of the university due to the effect of the supportive organizational culture dimension